How do you simplify #(6x^2y^2)(-xy^4)^5# leaving only positive exponents? Algebra Expressions, Equations, and Functions Variable Expressions 1 Answer sankarankalyanam Mar 14, 2018 Answer: #= (color(indigo)(- 6 x^7 y^22))# Explanation: #( 6x^2 y^2) * ( - xyy^4)^5# #=> (6 x^2y^2) * (-1)^5 * (xy^4)^5# #=> - (6x^2y^2) * (xy^4)^5 color(white)(aaa) # as #color(purple)((-1)^5 = -1# #=> - (6x^2y^2) * (x^5 y^20)# #=> - (6 x^2 x^5 y^2y20) # Rearranging terms. #=> - 6 x^(2+5) * y^(2 + 20) = (color(indigo)(- 6 x^7 y^22))# Related questions How do you write the variable expression for: a quotient of 2 and the sum of a number and 3 ? What are variables? What are variable expressions? How do you write variable expressions? How do you evaluate variable expressions? How do you simplify the expression #3x-x+4#? How do you write a quotient of a number and 6 as an expression? How do you evaluate the expression #2x+1# for #x=1#? How do you write a product of a number and 2 as an expression? How do you write 5 less than 2 times a number as a variable expression? See all questions in Variable Expressions Impact of this question 247 views around the world You can reuse this answer Creative Commons License